Osteoarticular Infections Caused by Non-Aspergillus Filamentous Fungi in Adult and Pediatric Patients: A Systematic Review. Issue 50 (December 2015) - Taj-Aldeen, Saad J.; Rammaert, Blandine; Gamaletsou, Maria; Sipsas, Nikolaos V.; Zeller, Valerie; Roilides, Emmanuel; Kontoyiannis, Dimitrios P.; Miller, Andy O.; Petraitis, Vidmantas; Walsh, Thomas J.; Lortholary, Olivier
Abstract : Abstract: Osteoarticular mycoses due to non- Aspergillus moulds are uncommon and challenging infections. A systematic literature review of non- Aspergillus osteoarticular mycoses was performed using PUBMED and EMBASE databases from 1970 to 2013. Among 145 patients were 111 adults (median age 48.5 [16–92 y]) and 34 pediatric patients (median age 7.5 [3–15 y]); 114 (79.7%) were male and 88 (61.9%) were immunocompromised. Osteomyelitis was due to direct inoculation in 54.5%. Trauma and puncture wounds were more frequent in children (73.5% vs 43.5%; P = 0.001). Prior surgery was more frequent in adults (27.7% vs 5.9%; P = 0.025). Vertebral (23.2%) and craniofacial osteomyelitis (13.1%) with neurological deficits predominated in adults. Lower limb osteomyelitis (47.7%) and knee arthritis (67.8%) were predominantly seen in children. Hyalohyphomycosis represented 64.8% of documented infections with Scedosporium apiospermum (33.1%) and Lomentospora prolificans (15.8%) as the most common causes. Combined antifungal therapy and surgery was used in 69% of cases with overall response in 85.8%. Median duration of therapy was 115 days (range 5–730). When voriconazole was used as single agent for treatment of hyalohyphomycosis and phaeohyphomycosis, an overall response rate was achieved in 94.1% of cases. Non- Aspergillus osteoarticular mycoses occur most frequently in children after injury and in adults after surgery. Accurate early diagnosis and long-course therapy (median 6 mo) with a combined medical-surgical approach may result in favorable outcome.